Strategy for Strengthening Character Education in Elementary School Children: Building a Generation with Noble Morals Qualitative Study at SD Negeri Planjan 01 Kesugihan - Eli Purwati; Wanda Nugroho Yanuarto (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to identify and analyze strategies for strengthening character education at SD Negeri Planjan 01 Kesugihan that are relevant to be applied to elementary school children in an effort to build a generation with noble character. Character education at the elementary school level has a fundamental role in laying the foundation for moral and ethical values for the further development of students. This study uses a qualitative approach through a literature review of various studies and related concepts. The data collection instruments in this study used questionnaires, observations and documentation and were then analyzed. The analysis includes the integration of character values in the curriculum, positive behavioral habits, utilization of learning media, the role of role models, and the potential for implementing innovative character education concepts. The subjects in this study included students, teachers and parents of students at SD Negeri Planjan 01 Kesugihan.Based on the results of initial observations conducted, there are still many students who show bad behavior, such as lack of manners in speaking with friends and teachers, and frequent disharmony during class hours. In the context of character education, the role of teachers is very important as idolized figures, as well as being a source of inspiration and motivation. The teacher's attitude and behavior will be very memorable for a student, so that the character, speech, and personality of the teacher become a reflection of the student. Teachers who are worthy of being role models, character education will be easy to build in an educational institution or school. Development in character formation requires exemplary behavior that is transmitted, intervention through the learning process, training, continuous habituation in the long term that is carried out continuously and reinforcement, and must be balanced with noble values.